Metodologija snovanja izvršilnega procesorja za 32-bitni računalniški sistem - Gerkeš, Maksimiljan (Informatica (Ljubljana), 1984)
Article describes design methods used for a 32-bit execution processor prototype design. 32-bit execution processor is relatively high speed universal operator support for a 32-bit computer system based on a complex instruction set. At the beginning we define execution processor as a universal three operand operator. With stepwise refinement it is then decomposed into lower level parts. In and outcomming parameter values are written into I/O register set which is completed with working register set for holding partial results, generated with interpreted operations, defined by complex instruction set. Because of operations interpretation microprogrammed control structure is defined based on the characteristic features of microprogramms.
Keywords: 32-bitni procesorji; izvršilni procesorji